Understanding facilitators, barriers, and solutions in developing and implementing an interprofessional education module for chronic disease management in Vietnam - Nguyen, Thi Thanh Huyen; Nguyen, Minh Tam; Johan, Wens; Martin, Valcke; Huynh, Van Chuong; Le, Van Chi; Nguyen, Lo; Ho, Dac Truong An; Ho, Anh Hien; Le, Ho Thi Quynh Anh; Nguyen, Vu Quoc Huy; Giannoula, Tsakitzidis (Tạp chí Y Dược Huế, 2025)
Background: Interprofessional education (IPE) in developing countries remains challenging. The University of Medicine and Pharmacy, Hue University, developed an IPE module for chronic disease management in Vietnam, incorporating classroom-based interactive learning, simulation with standardised patients, clinical practice, and home visits. This study explores lecturers’ experiences to identify facilitators, barriers, and solutions in the development and implementation of the module. Methods: An exploratory qualitative method with focus group interviews was conducted with 25 lecturers from 11 disciplines involved in this IPE module. Data were thematically analysed using NVivo 1.7.2 software. Results: Four main themes emerged, including ‘motivation’, ‘advantages’, ‘challenges’, and ‘suggestions’. Facilitators of successful implementation included strong institutional support, high lecturer motivation, expert-led faculty development, and robust collaboration between the university and primary healthcare facilities. Major barriers involved challenges in delivering feedback on interprofessional care plans, logistical complexities related to patient and standardised patient preparation, resource and time constraints, and the intensive demands of new assessment tools. To overcome these challenges, strategic solutions were employed, such as recruiting volunteer patients, training standardised patients, designing complex case scenarios around chronic disease and multimorbidity, increasing module offerings per semester, training faculty in assessment methods, hosting IPE conferences to recruit additional lecturers, and integrating the module into the formal academic curriculum. Conclusion: Successful IPE implementation requires recognising context-specific facilitators and barriers and tailored solutions. A structured seven-step process is recommended, offering a scalable and adaptable model for other institutions in Vietnam and similar settings globally.